Direct effects of exercise on kynurenine metabolism in people with normal glucose tolerance or type 2 diabetes. Issue 7 (1st May 2016) - Mudry, Jonathan M.; Alm, Petter S.; Erhardt, Sophie; Goiny, Michel; Fritz, Tomas; Caidahl, Kenneth; Zierath, Juleen R.; Krook, Anna; Wallberg‐Henriksson, Harriet
Abstract: Background: Systemic kynurenine levels are associated with resistance to stress‐induced depression and are modulated by exercise. Tryptophan is a precursor for serotonin and kynurenine synthesis. Kynurenine is transformed into the neuroprotective catabolite kynurenic acid by kynurenine aminotransferases (KATs). PGC‐1α1 increases KAT mRNA and induces kynurenic acid synthesis. We tested the hypothesis that skeletal muscle PGC‐1α1 /KAT‐kynurenine pathway is altered by exercise and type 2 diabetes. Method: Skeletal muscle and plasma from men with normal glucose tolerance ( n  = 12) or type 2 diabetes ( n  = 12) was studied at rest, after acute exercise and during recovery. Tryptophan, Kynurenine and kynurenic acid plasma concentration were measured as well as mRNA of genes related to exercise and kynurenine metabolism. Results: mRNA expression of KAT1, KAT2 and PPARα was modestly reduced in type 2 diabetic patients. In response to exercise, mRNA expression of KAT4 decreased and PGC‐1α1 increased in both groups. Exercise increased plasma kynurenic acid and reduced kynurenine in normal glucose tolerance and type 2 diabetic participants. Plasma tryptophan was reduced and the ratio of [kynurenic acid] * 1000/[kynurenine] increased in both groups at recovery, suggesting an improved balance between neurotoxic and neuroprotective influences. Tryptophan and kynurenine correlated with body mass index, suggesting a relationship with obesity. Conclusions: Acute exercise directly affects circulating levels of tryptophan, kynurenine and kynurenic acid, providing a potential mechanism for the anti‐depressive effects of exercise. Furthermore, exercise‐mediated changes in kynurenine metabolism are preserved in type 2 diabetic patients. Copyright © 2016 John Wiley & Sons, Ltd.